Driving Global Expansion: How China’s Strategic Intervention Propels It’s Electric Vehicle Industry In Southeast Asia From 2016-2023: English - Grace Octavia Ilanunu; Reza Triarda (CV. AFDIFAL MAJU BERKAH, 2026)
This article examines how strategic state intervention propelled the global dominance of China’s electric vehicle (EV) industry and its subsequent expansion into Southeast Asia. Drawing on Ha-Joon Chang’s framework of industrial policy, the study argues that the Chinese EV case must be understood not as a free-market phenomenon driven by regional demand, but as a form of structural state intervention that matured domestic productive capacity before projecting it abroad. Methodologically, the study applies a qualitative single case study design, with data collected through a structured desk review of official policy documents, industry reports, and peer-reviewed literature, and analyzed through a theoretical thematic analysis explicitly driven by the industrial policy framework. The results demonstrate that strategic intervention facilitated this dominance through three interrelated mechanisms: value creation and value capture through conditional subsidies and mandated joint ventures; the countering of financialization by compelling the reinvestment of corporate surplus into research and development (R&D); and the expansion of policy space by redirecting surplus capacity toward Southeast Asia. The discussion analyzes these results through the three dimensions of Chang and Andreoni’s framework, namely new patterns of accumulation with value creation and value capture, financialization, and the new imperialism, and situates them within the wider scholarship on state-led industrialization and global value chains. It contends that the resulting configuration reproduces an asymmetrical division of labor in which Southeast Asian economies occupy assembly positions while core technologies remain under Chinese control. The article concludes that industrial policy remains a viable instrument for simultaneously building technological self-reliance, achieving cost efficiency, and securing a commanding position within international supply chains.